2020
DOI: 10.1038/s41598-020-63664-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of new genetic resources for faba bean (Vicia faba L.) breeding through the discovery of gene-based SNP markers and the construction of a high-density consensus map

Abstract: faba bean (Vicia faba L.) is a pulse crop of high nutritional value and high importance for sustainable agriculture and soil protection. With the objective of identifying gene-based Snps, transcriptome sequencing was performed in order to reduce faba bean genome complexity. A set of 1,819 genebased Snp markers polymorphic in three recombinant line populations was selected to enable the construction of a high-density consensus genetic map encompassing 1,728 markers well distributed in six linkage groups and spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 58 publications
(62 reference statements)
0
55
2
Order By: Relevance
“…Using exome capture, which combines single nucleotide polymorphism (SNP) discovery and genotyping, 1.9‐M SNPs were detected for the pea architecture and multistress (AMS) collection and 1.7 M for the faba bean collection. By sequencing of the faba bean transcriptomes of four parental lines of the RIL populations, 104,000 SNPs were detected, and 2,000 of those have been used for genotyping of segregating populations using genotyping by capture technique (Carrillo‐Perdomo et al, 2020).…”
Section: Genetic and Genomic Determinants Of Resistance To Major Stresses In Pea And Faba Beanmentioning
confidence: 99%
“…Using exome capture, which combines single nucleotide polymorphism (SNP) discovery and genotyping, 1.9‐M SNPs were detected for the pea architecture and multistress (AMS) collection and 1.7 M for the faba bean collection. By sequencing of the faba bean transcriptomes of four parental lines of the RIL populations, 104,000 SNPs were detected, and 2,000 of those have been used for genotyping of segregating populations using genotyping by capture technique (Carrillo‐Perdomo et al, 2020).…”
Section: Genetic and Genomic Determinants Of Resistance To Major Stresses In Pea And Faba Beanmentioning
confidence: 99%
“…It contained 687 SNP markers on six linkage groups, each presumed to correspond to one of the faba bean chromosomes. Carrillo-Perdomo et al (2020) recently reported the most saturated consensus genetic map to date: it was constructed using three mapping populations and encompassed 1,728 SNP markers distributed in six linkage groups. Solid proof of macro-synteny was also observed between this map and the most closely-related legume species that have been sequenced.…”
Section: Genetic Mapsmentioning
confidence: 99%
“…However, from these reported transcriptome datasets, only limited DNA sequence data are available in public databases (Mokhtar et al, 2020). Additionally, the development of high-density genetic maps derived from multiple populations and gene-based molecular markers, particularly those developed by Webb et al (2016) and Carrillo-Perdomo et al (2020), have paved the road to marker-assisted selection (MAS) and gene discovery. For example, the elucidation of the biosynthetic pathway for the pyrimidine glycosides vicine and convicine (v-c) (Björnsdotter et al, 2020), which have been the main factors limiting faba bean cultivation and usage in many warm regions, was not possible without the combination of transcriptome data (Ray et al, 2015) and gene-based comparative mapping approaches (Khazaei et al, 2015;.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile further such consensus maps have become known (e.g. Carrillo‐Perdomo et al., 2020; Ocaña‐Moral et al., 2017; Sudheesh et al., 2019). Although previously various types of markers were employed to detect and map QTL for Ascochyta resistance in faba beans (Avila et al., 2004; Cruz‐Izquierdo et al., 2012; Díaz‐Ruiz et al., 2009; Ellwood et al., 2008; El‐Rodeny et al., 2014; Kaur et al., 2014; Roman et al., 2003), today, mainly SNPs are used for such analyses.…”
Section: Introductionmentioning
confidence: 99%